The Effect of Jigsaw Reading in Enhancing Students’ Understanding at UIN Sunan Ampel Surabaya - Sanjaya, Muchammad Isa Zidan; Arzaqina, Fina (ICONELT, 2022)
The focus of this study is to investigate the effect of jigsaw reading in enhancing students comprehension, generally in all materials. Survey research was used as the research method, and for the research design, the researcher used quantitative research. The research subjects were 31 fifth semester students of UIN Sunan Ampel Surabaya who were picked randomly, and considered to have been experienced online learning for 2 years. Questionnaires consist of sixteen questions were used as the instruments which dealing with students’ perspectives in having online learning. After distributing questionnaires and analyzing the data, it has been found out that there were fierce battle going on between neutral students and agree students since they are still unsettled in choosing online or offline learning since both of them have their own characteristics. In conclusion, this study found that most of the students agreed that having online learning can upgrade their materials understanding.